WORK-LIFE BALANCE AND ORGANIZATIONAL CITIZENSHIP BEHAVIOUR ON PERFORMANCE - Aprilianto, Jiwanda Shondra; Lindiawati, Lindiawati; Setia, Shinta (Kesatuan Press, 2025)
This study addresses the challenge of maintaining optimal team member performance amid environmental demands and job stress in community health centers. Employees often face high workloads, complex service demands, and limited resources, which can disrupt their work-life balance and affect their engagement beyond formal job roles. In such contexts, organizational citizenship behavior (OCB), voluntary actions that support organizational functioning, becomes critical in sustaining performance. This research examines how work-life balance, work environment, and job stress affect team member performance, with OCB as a mediating factor, at Community Health Centers (Puskesmas) in North Surabaya, primarily at the Sawah Pulo, Tambak Wedi, and Wonokusumo Community Health Centers. The findings show that maintaining a good balance between personal life and work and a supportive work environment can increase OCB and performance. Conversely, job stress shows minimal impact on OCB and performance, indicating that other factors may buffer its effects. The study underscores the strategic value of cultivating supportive organizational conditions and encouraging extra-role behaviors to drive better outcomes in public health services.